STIM1 R304W in mice causes subgingival hair growth and an increased fraction of trabecular bone. (January 2020) - Gamage, Thilini H.; Lengle, Emma; Gunnes, Gjermund; Pullisaar, Helen; Holmgren, Asbjørn; Reseland, Janne E.; Merckoll, Else; Corti, Stefania; Mizobuchi, Masahiro; Morales, Raul J.; Tsiokas, Leonidas; Tjønnfjord, Geir E.; et al.
Graphical abstract: Highlights: The kyphosis and reduced number of ribs in Stim1 R304W mice highlight the critical role of SOCE during skeletal development Stim1 R304W mice also show decreased thickness of cortical bone and increased trabecular bone volume. The reduced bone marrow cavity in Stim1 R304W mice may result in splenomegaly extending the hematopoietic organ Subgingival hair growth on the lower incisors in Stim1 R304W mice indicates dysregulated Ca 2+ driven epithelial cell fate Abstract: Calcium signaling plays a central role in bone development and homeostasis. Store operated calcium entry (SOCE) is an important calcium influx pathway mediated by calcium release activated calcium (CRAC) channels in the plasma membrane. Stromal interaction molecule 1 (STIM1) is an endoplasmic reticulum calcium sensing protein important for SOCE. We generated a mouse model expressing the STIM1 R304W mutation, causing Stormorken syndrome in humans. Stim1 R304W/R304W mice showed perinatal lethality, and the only three animals that survived into adulthood presented with reduced growth, low body weight, and thoracic kyphosis. Radiographs revealed a reduced number of ribs in the Stim1 R304W/R304W mice. Microcomputed tomography data revealed decreased cortical bone thickness and increased trabecular bone volume fraction in Stim1 R304W/R304W mice, which had thinner and more compact bone compared to wild type mice. The Stim1 R304W/+ mice showed an intermediate phenotype. Histological analyses showed that the Stim1 R304W/R304W mice had abnormal bone architecture, with markedly increased number of trabeculae and reduced bone marrow cavity. Homozygous mice showed STIM1 positive osteocytes and osteoblasts. These findings highlight the critical role of the gain-of-function (GoF) STIM1 R304W protein in skeletal development and homeostasis in mice. Furthermore, the novel feature of bilateral subgingival hair growth on the lower incisors in the Stim1 R304W/R304W mice and 25 % of the heterozygous mice indicate that the GoF STIM1 R304W protein also induces an abnormal epithelial cell fate.